Compliance of Haditha Dam in Iraq to the International Standards for Surveillance and Monitoring (Journal of Engineering, 2024)
Dams are mega structures that retain huge volumes of water and their safety is important to national security, economy, and public interest. In this study, the types of regular measurements with their recorded value for Haditha Dam were checked for compliance with the standard international surveillance and monitoring procedures such as the procedures of the International Commission on Large Dams (ICOLD), the United States Bureau of Reclamation (USBR)and other to ensure safe dam operation and to avoid the scenario of the Derna Dam break, in Libya that occurred in September 2023. The result shows that the highest recorded settlement was found at station 41 on the left side of the dam body exceeding the design criteria (219 mm) by about 51 %, the frequency of measurement does not comply with the required international standards. There are 7 cells of pore pressure that exceeded the design criteria and the greatest percentage of exceedance was 21.57 % was found at pore pressure number 995. For piezometer reading, the percentage exceedance was 9.1% and it was found on the left side at piezometers number 58-8. The highest percentage of movement 62 % was found at join meter device number D18. The recorded seepage rate through the dam was found within the permitted limits. The visual inspection followed at Haditha Dam was not according to the standard required inspection.